Deep Historicities. Issue 2 (17th February 2022) - Rademaker, Laura; Silverstein, Ben
Abstract : In seeking to understand the deep past, the knowledges of First Nations peoples and of the various academic disciplines can seem incommensurable. In this essay, we argue the concept of "historicities", that is, the encultured ways of narrating and conceiving of the past offers to enrich the study of deep history. Sensitivity to the various ways the past is remembered and understood, as well as the ways in which these historicities are dialogically and relationally constructed, offers ways of bringing distinct accounts of the deep past into conversation. Through closely reading various narrations of deep histories of the Tiwi Islands, we suggest ways in which historicities might be understood as coexisting and in relation, without reducing their accounts to a single universalizable story of the past or hierarchy of knowledges. This special issue further explores decolonizing challenges to ways of knowing the deep past from a range of disciplinary perspectives.